Equations with Random Gaussian Operators with Unbounded Mean Value - Vlasenko, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider an equation in a Hilbert space with a random operator represented as a sum of a deterministic, closed, densely defined operator and a Gaussian strong random operator. We represent a solution of an equation with random right-hand side in terms of stochastic derivatives of solutions of an equation with deterministic right-hand side. We consider applications of this representation to the anticipating Cauchy problem for a stochastic partial differential equation.